Cerebral Microbleeds, CSF p-Tau, and Cognitive Decline: Significance of Anatomic Distribution - Chiang, G.C.; Cruz Hernandez, J.C.; Kantarci, K.; Jack, C.R.; Weiner, M.W.; for the Alzheimer's Disease Neuroimaging Initiative (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Cerebral microbleeds are associated with aging, hypertension, and Alzheimer disease. Microbleeds in a lobar distribution are believed to reflect underlying amyloid angiopathy, whereas microbleeds in the deep gray matter and infratentorial brain are commonly seen with hypertension. However, it is unknown how microbleeds in either distribution are related to Alzheimer pathogenesis. The purpose of this analysis was to test whether lobar and deep gray/infratentorial microbleeds demonstrate differential associations with CSF amyloid-β and phosphorylated tau 181 protein levels and longitudinal cognitive decline.MATERIALS AND METHODS: A total of 626 subjects (151 cognitively normal, 389 with mild cognitive impairment, and 86 with Alzheimer disease) from the Alzheimer's Disease Neuroimaging Initiative who had undergone 3T MR imaging and lumbar puncture were included in the analysis. The number and location of microbleeds were assessed visually. Associations between lobar or deep gray/infratentorial microbleeds with CSF amyloid-β levels, abnormal CSF phosphorylated tau 181 protein levels, and longitudinal cognitive decline were assessed by using ordinary least-squares, logistic, and mixed-effects regression models while adjusting for covariates.RESULTS: Having ≥3 lobar microbleeds was associated with lower levels of CSF amyloid-β (P = .001). After adjusting for CSF amyloid-β level, lobar microbleeds were independently associated with a higher likelihood of having an abnormal CSF phosphorylated tau 181 protein level (P = .004). Lobar microbleeds were associated with accelerated longitudinal cognitive decline (P = .007). Deep gray/infratentorial microbleeds revealed no significant associations.CONCLUSIONS: The distribution of microbleeds revealed different associations with amyloid-β and phosphorylated tau 181 protein levels and cognition. Lobar and deep gray/infratentorial microbleeds should be considered separately with regard to Alzheimer disease pathogenesis.Aβamyloid-βADAlzheimer diseaseADASAlzheimer Disease Assessment ScaleADNIAlzheimer's Disease Neuroimaging InitiativeAPOEapolipoprotein Ep-tauphosphorylated tau 181 protein